Analysis of Indicators for Assessing the Risk of Progression from PACS to APAC and the Degree of Intraocular Pressure Elevation in APAC Using AS-OCT - Rumin Zhao; Qiaofang Du; Yunlong Wu; Wenhui Geng; Zijian Zhang; Bojun Zhao (Journal of Ophthalmology)
Objective. The aim of this study is to quantify anterior chamber parameters to provide potential risk indicators for evaluating the progression of primary angle-closure suspect (PACS) eyes to acute primary angle closure (APAC) and the degree of intraocular pressure elevation in patients with APAC utilizing anterior segment optical coherence tomography (AS-OCT). Methods. Tomey CASIA2 AS-OCT was used to quantitatively measure various anterior chamber parameters, including anterior chamber depth (ACD), anterior chamber volume (ACV), lens thickness (LT), lens vault (LV), iris-trabecular contact index (ITC), iris thickness (IT), iris volume (IV), iris curvature (IC), iris area (IA), and iris thickness (IT), in APAC eyes (30 eyes) and contralateral PACS eyes (30 eyes) of 30 patients. The differences in these parameters between the two groups and their relationship with intraocular pressure were analyzed. Results. Compared to the PACS group, the APAC group exhibited significantly smaller IA and IC, and significantly larger pupil diameter (PD) and ITC (P<0.05). There were no statistically significant differences in ACV, ACD, ACW, ACA, LV, IV, and IT750/2000 between the two groups. In APAC eyes, multivariable linear regression analysis showed a significant negative correlation between intraocular pressure and IV (β = −1.85; 95% confidence interval: −2.77 to −0.93; P=0.001), while no correlation was found in PACS eyes. In all 60 eyes, LT showed a negative correlation with ACV, ACD, ACA, and nasal IT750, and a positive correlation with LV and nasal IC. Conclusion. AS-OCT has multiple advantages in evaluating various anterior chamber parameters in patients with glaucoma. IA may serve as a predictive indicator of the progression of eyes from PAC or APAC. A significant negative correlation was found between intraocular pressure and IV during APAC attacks. LT can be considered a predictive factor for the occurrence of primary angle-closure disease.